UPAYA MENINGKATKAN HASIL BELAJAR SISWA TENTANG PERKALIAN DENGAN MENGGUNAKAN MEDIA GAMBAR PADA SISWA KELAS II DI SD N 24 PAKAN SINAYAN - Widiastuti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research is motivated by the low learning outcomes of students caused by the lack of proper learning models used in learning mathematics so that in the learning process the majority of students are still passive and lack interaction. This study aims to determine how much influence the use of learning using media images has on the learning outcomes of students in Class II SD N 24 Pakan Sinayan. This type of research is quantitative research with the subjects in this study being grade II students at SD N 24 Pakan Sinayan with a total of 22 students. This research was conducted in two cycles. Each cycle consists of two meetings. Data collection techniques using observation, tests and non-tests. Research data were analyzed using qualitative descriptive techniques to analyze the results of observations and quantitative descriptive techniques to analyze test results. Based on the results of the 2nd cycle research, very satisfying results were obtained where there was an increase in student learning outcomes from cycle 1 to cycle 2. Thus it can be concluded that the use of Media Pictures has an effect on student learning outcomes in Mathematics learning in Elementary Schools.